The Habsburg Monarchy from a Roman Perspective: Potential Insights of the “Nuncial Reports from Germany” for International Historical Research (Theatrum historiae, 2019)
rom the very beginning of the edition “Nuncial reports from Germany” in the late nineteenth century, the publication of sources was extended beyond the century of Reformation to the time of the Thirty Years’ War. The fourth series, dedicated to the first half of the seventeenth century, was finished in 2016. There are six substantial volumes which document the core phase (around 1630) of the Thirty Years’ War with its decisive change to the disadvantage of the emperor, the Habsburgs and the Catholic faction of the Holy Roman Empire up to the intensive efforts to make peace, the Peace of Prague in 1635 and the concurrent European extension of the Thirty Years’ War with Sweden’s and France’s entry into the war in 1630/1635. With these volumes, a cohesive documentation of sources of European rank was achieved. 2018 marked the 400th anniversary of the outbreak of the war, thus it is worth looking at this edition as a prime collection of sources of European history, particularly of the Papal–Habsburg relations at the height of the Thirty Years’ War.
Keywords: Thirty Years’ War; Peace of Westphalia; papal diplomacy; Imperial court; Habsburg–Roman relations